Synergistic siRNA Loading of Extracellular Vesicles Enables Functional Delivery into Cells. Issue 12 (25th October 2022) - Roerig, Josepha; Mitrach, Franziska; Schmid, Maximilian; Hause, Gerd; Hacker, Michael C.; Wölk, Christian; Schulz‐Siegmund, Michaela
Abstract: RNA interference opened new approaches for disease treatment but safe and efficient cell delivery remains a bottleneck. Extracellular vesicles (EVs) are known to naturally shuttle RNA. Due to their potent cell internalization and low‐cost scalability, milk‐derived EVs in particular are considered promising RNA delivery systems. However, low drug loading currently impedes their use. Here, innovative exogenous loading strategies for small interfering RNA (siRNA) are explored and systematically compared regarding encapsulation efficiency, loading capacity, and loading concentration. Firstly, siRNA is pre‐accumulated in liposomes or stabilized calcium phosphate nanoparticles (CaP‐NP). The selected systems, which exhibited neutral or negative zeta potentials, are then applied for EV loading. Secondly, EVs are concentrated and applied to protocols known for liposome loading: dehydration‐rehydration of vesicles, based on freeze‐drying, and mixing by dual asymmetric centrifugation (DAC) after ultracentrifugation. Additionally, DAC after EV ultracentrifugation is combined with CaP‐NP leading to a synergistic loading performance. The balance between energy input for siRNA loading and EV integrity is evaluated by monitoring the EV size, marker proteins, and morphology. For the EV‐based siRNA formulation via DAC plus CaP‐NP, EV properties are sufficiently maintained to protect the siRNA from degradation and deliver cell‐death siRNA dose‐dependently in Caco‐2 cells. Abstract : Extracellular vesicles (EVs) are investigated as potential delivery systems for small interfering RNA (siRNA), but loading is currently inefficient. Here, different exogenous loading strategies are explored with pre‐accumulating siRNA in stabilized calcium phosphate nanoparticles and subsequent dual asymmetric centrifugation leading to synergistic loading. With this novel strategy, EV characteristics are maintained to deliver siRNA dose‐dependently into cells.